(untitled) (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Non-contrasted computed tomography scan for kidney, ureter, and bladder (CT KUB) for diagnosis of urolithiasis is important for accurate diagnosis, followup, and management. Unlike USG, CT KUB has more diagnostic yield in urolithiasis and other incidental findings. This study aims to evaluate the use of the CT KUB in suspected urolithiasis, presented with severe flank pain. Method: A retrospective observational study was carried out in the Department of Radiology and Imaging, Patan Hospital, Nepal.TheCT KUB reports of patients with suspected urolithiasis from a period of 3 years from Jan 2017 to Jan 2020 were analyzed for evidence of urolithiasis and secondary signs of obstruction as ‘diagnostic’ of CT KUB. Other incidental radiological findings were further analysed and categorized into urinary and extra-urinary. Ethical approval was obtained.Association of USG and CT KUBwas analysed using Chi-square test,with p value<0.05considered statistically significant. Result: Total of 414 CT KUB reports were analysed, 230(55.6%) males, 314 patients had USG before CT KUB. Considering CT KUB as a gold standard for diagnois of urolithiasis, the accuracy of ultrasound was found to be 85.03% and sensitivity is 94.09% and specificity of 27.9%. Conclusion: Majority of the patients included in the study had ultrasound done before CT KUB. The sensitivity of ultrasound was significant considering CT KUB as a gold standard in diagnosis of urolithaisis.